A 3-d micromechanical model of cyclic plasticity in a fiber-reinforced metal matrix composite - Liu, Y.-F. (Journal of materials science letters, 2001)
Fiber-reinforced metal matrix composites (MMCs) have attractive mechanical properties which offer the potential for advanced structural applications. Matrix plastic deformation is one common damage pattern in MMCs and has been molded mostly based on 2-d elasticity with certain exceptions. In this study, a 3-d micromechanical finite element model is developed to study the plastic deformation of a SCS-6 fiber reinforced-titanium alloy composite during cyclic loading. A new implication of the plastic deformation is provided regarding the fatigue crack growth in this composite.